Interaction between physicians and the pharmaceutical industry: A scoping review for developing a policy brief - Ehsan Zarei; Amir Ghaffari; Ali Nikoobar; Shayan Bastami; Hasan Hamdghaddari (Frontiers Media S.A., 2023)
BackgroundPayments to physicians by the pharmaceutical industry are common, but recent evidence shows that these payments influence physician prescribing behavior in the form of increased prescription of brand-name drugs, expensive and low-cost drugs, increased prescription of payer company drugs, etc. Considering that these payments increase drug costs for patients and health systems, there is a public interest in controlling them. Therefore, this study aimed to identify and propose policy options for managing physician-pharmaceutical industry interactions in the context of Iran's health system.MethodsIn the first phase, a systematic search was conducted to identify relevant policies and interventions in Web of Science, PubMed, and ProQuest databases from 2000 to 2022. Then, the opinions of the research team and an expert group (physicians, health policy and transparency experts, and industry representatives) were used to categorize the interventions and propose policy options along with their advantages, disadvantages, and implementation considerations.ResultsIn the search, 579 articles were retrieved, and 44 articles were found suitable for the final analysis. Twenty-nine interventions and strategies were identified, and based on these; Five policy options were identified: prohibition, restriction, physician self-regulation, voluntary industry disclosure, and mandatory industry disclosure.ConclusionThe proposed policies in our study include advantages, challenges, and implementation considerations based on up-to-date evidence that can help policymakers use them to manage COI in physician-pharmaceutical industry interactions in Iran's health system. A combination of measures seems to help manage COI: firstly, using self-regulating physicians and industry to institutionalize transparency, and in the next step, implementing mandatory industry disclosure policies and establishing restrictions on some financial interactions.